Mitovirus and Mitochondrial Coding Sequences from Basal Fungus Entomophthora muscae - Nibert, Max; Debat, Humberto; Manny, Austin; Grigoriev, Igor; De Fine Licht, Henrik (Viruses, 2019)
Fungi constituting the Entomophthora muscae species complex (members of subphylum Entomophthoromycotina, phylum Zoopagamycota) commonly kill their insect hosts and manipulate host behaviors in the process. In this study, we made use of public transcriptome data to identify and characterize eight new species of mitoviruses associated with several different E. muscae isolates. Mitoviruses are simple RNA viruses that replicate in host mitochondria and are frequently found in more phylogenetically apical fungi (members of subphylum Glomeromyoctina, phylum Mucoromycota, phylum Basidiomycota and phylum Ascomycota) as well as in plants. E. muscae is the first fungus from phylum Zoopagomycota, and thereby the most phylogenetically basal fungus, found to harbor mitoviruses to date. Multiple UGA (Trp) codons are found not only in each of the new mitovirus sequences from E. muscae but also in mitochondrial core-gene coding sequences newly assembled from E. muscae transcriptome data, suggesting that UGA (Trp) is not a rarely used codon in the mitochondria of this fungus. The presence of mitoviruses in these basal fungi has possible implications for the evolution of these viruses.